Intencje edukacyjne pragmatycznych znaczeń w Sztuce doczesnej mądrości Baltasara Graciána - Wojnowski, Kazimierz (Biuletyn Historii Wychowania, 2023)
Baltasar Gracián’s views revolved around the motivation of moral axiology in reference to the cognitive knowledge of reason and the practical knowledge of reason, by which individuals achieve effective results. He believed that knowledge of motivation, strategies and tactics for successful goal achievement should be imparted in education, while wisdom is expressed by effective long-term and permanent results of reasonable actions. Behavioral strategies motivated by moral axiology result in increased human spiritual and material well-being in society, and education in this area contributes to knowledge spread and moral progress. Temporal wisdom is both life wisdom and worldly wisdom; the former belongs to the human nature of life and is a driving force behind the creation of a better human world.